Negotiating the Landscape : Environment and Monastic Identity in the Medieval Ardennes - Arnold, Ellen Fenzel (Book collections on Project MUSE., 2013)
The author draws upon a rich archive of charters, property and tax records, correspondence, miracle collections, and saints' lives to explore the ways in which interaction with the natural world affected the "environmental imagination" and identity of the Benedictine monks of Stavelot-Malmedy in the medieval Ardennes.